1989
DOI: 10.1099/0022-1317-70-4-955
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleotide Sequence of Satellite RNA in Grapevine Fanleaf Virus, Strain F13

Abstract: SUMMARYThe nucleotide sequence of cDNA copies of grapevine fanleaf virus (strain F13) satellite RNA has been determined. The primary structure obtained was 1114 nucleotides in length, excluding the poly(A) tail, and contained only one long open reading frame encoding a 341 residue, highly hydrophilic polypeptide of Mr 37 275. The coding sequence was bordered by a leader of 14 nucleotides and a 3'-terminal noncoding region of 74 nucleotides. No homology has been found with small satellite RNAs associated with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
6

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 25 publications
0
38
0
6
Order By: Relevance
“…The global similarity between these two sequences is close to 80%, with the highest degree of homology within the 130 first nucleotides. The sequence UGAAAAUUU from nt 2 to 10 is part of the 5' consensus sequence already reported for nepovirus RNAs (Fuchs et al, 1989).…”
Section: Sequence Homologies Between Rna1 and Rna2 Of Gfl V And Othermentioning
confidence: 99%
See 2 more Smart Citations
“…The global similarity between these two sequences is close to 80%, with the highest degree of homology within the 130 first nucleotides. The sequence UGAAAAUUU from nt 2 to 10 is part of the 5' consensus sequence already reported for nepovirus RNAs (Fuchs et al, 1989).…”
Section: Sequence Homologies Between Rna1 and Rna2 Of Gfl V And Othermentioning
confidence: 99%
“…The length of GFLV RNAs was estimated at about 6800 nucleotides (nt) upon gel electrophoresis under denaturing conditions for RNA1 (Pinck et al, 1988) and at 3774 nt for RNA2 after cloning and complete sequencing (Serghini et al, 1990). An additional smaller satellite RNA (Pinck et al, 1988) has also been identified and is composed of 1114 nt (Fuchs et al, 1989). When translated in vitro in a wheatgerm extract each viral RNA induces the synthesis of a polyprotein corresponding to its entire coding capacity, with apparent Mr values of 225K for RNA1 (Pinck et al, 1988), 122K for RNA2 (Serghini et al, t Permanent address: Escola Tecnica Federal de Quimica do Rio de Janeiro, 121 Rua Senador Furtado, 20270 Rio de Janeiro, Brasil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since M2R was derived from MaR by cleavage at the unique XmnI site (position 8, Fig. I a), thereby breaking the VpG consensus sequence identified by Fuchs et al (1989), MzR lacked these eight nucleotides at the 5' end. M3R contains the authentic satellite RNA sequence.…”
Section: Transcript Structure and Synthesismentioning
confidence: 99%
“…Furthermore, the 5'-terminal 11 nucleotides of this satellite RNA (UAUGAAAAAUU) fit the 5' end consensus sequence of nepoviral RNAs noted by Fuchs et al, (1989). ArMV satellite RNA encodes a polypeptide of 360 amino acids with an Mr of 39K (Liu et al, 1990), which is the major translation product in rabbit reticulocyte lysates (Hellen, 1987).…”
Section: Introductionmentioning
confidence: 99%